Dual Returns to Experience - Jose Garcia-Louzao; Laura Hospido; Alessandro Ruggieri (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this paper we study how labor market duality affects human capital accumulation and wage trajectories of young workers. Using rich administrative data for Spain, we follow workers since their entry into the labor market to measure experience accumulated under different contractual arrangements and we estimate their wage returns. We document lower returns to experience accumulated in fixed-term contracts compared to permanent contracts and show that this difference is neither due to unobserved firm heterogeneity nor match quality. Instead, we provide evidence that the gap in returns is due to lower human capital accumulation while working under fixed-term contracts. In line with skill-learning complementarity, our results suggest that the widespread use of fixed-term work arrangements reduces skill acquisition of high-skilled workers, holding back life-cycle wage growth by up to 16 percentage points after 15 years since labor market entry.
Keywords: J30; J41; J63; 330; labor market duality; human capital; earnings dynamics